REFLEKSI PENDIDIKAN NILAI BANGSA KITA - Agus Triyanto (Paradigma, 2006)
discussion in this article starts from the emergence of a variety of problems and global issues such as violation of human rights, multi-cultural-ethnic-religious reality, life environment, world peace, violence phenomena, and drug abuse which indispensably make educational practitioners think about an appropriate educational system capable of facing challenges. Therefore, an educational system focusing on moral value internalization emphasizing the aspect of universal humanism is important. Such a system should be adjusted to our needs in order for us as a nation to be able to face every challenge. The past education was deemed to fail to create people capable of individualizing and participating. As a result, our educational outputs are not only poor in skill and intellectual capacity but also fragile in character and morality. A national problem arising is not only unemployment and alumni’s poor capability but also a threat of moral decadence and criminality.The fact that the reform euphoria brings about effects on all aspects ofthe nation’s life, initially directed towards substantial matters, shows thatit still needs a long struggle to attain the reform objective. In fact, ournation needs not only characters with morality but also those withintellect, capable of thinking clearly and profoundly, idealistic andrealistic, and having a long-term vision. Those with intellect are able tosee the invisible, to see what is behind an emergent phenomenon, and toraise appropriate critical questions. Not all people are able to see avariety of moral problems that are usually behind emergent phenomena.The conclusion of this article is that to prevent moral values prevalent insociety from extinction, the society itself has to transfer them to the nextgeneration. A way to do so is education. Through education, the societyteaches knowledge, concepts of live, norms, and attitudes in social life,and teaches how to behave in social life, nation life, and government life.Key words : nation, value education, character, moral